The effect of career information service on improving students’ career understanding - Tampasera Datar; Ahmad Ahmad (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
The study aims at discovering description to career understanding of before and after treatment and at discovering career information service has an influence on the career understanding of students. This type of research is a quantitative of research type with an experimental research design of true experimental type. The sampling technique uses random sampling technique with the lottery method. Data collection techniques used two tools, namely the scale of social empathy and observation. Data analysis techniques used descriptive data analysis and inferential data analysis. The results showed that: (1) The level of career understanding of students at before being treated in this case career information services were in the low category, but after being treated the level of career understanding of students had increased or were in the very high category. (2) Career information services have an influence in improving student’s career understanding. This means that if the career information service is implemented it will help improve student’s career understanding.